2017
DOI: 10.1021/acs.jmedchem.7b00883
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Series of Tankyrase Inhibitors by a Hybridization Approach

Abstract: A structure-guided hybridization approach using two privileged substructures gave instant access to a new series of tankyrase inhibitors. The identified inhibitor 16 displays high target affinity on tankyrase 1 and 2 with biochemical and cellular IC values of 29 nM, 6.3 nM and 19 nM, respectively, and high selectivity toward other poly (ADP-ribose) polymerase enzymes. The identified inhibitor shows a favorable in vitro ADME profile as well as good oral bioavailability in mice, rats, and dogs. Critical for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 30 publications
(83 reference statements)
0
46
0
Order By: Relevance
“…between ring keto and SER1221 hydroxyl in the nicotinamide subpocket, amide keto and TYR1213 backbone keto in the adenosine subpocket, while exhibited π‐π stacking/hydrophobic interactions with binding site amino acids, namely TYR1224, HIS1184, PHE1188 and HIS1201. These interactions are reported to be vital for enzyme inhibition based on the X‐ray structures of active compounds . However, as expected, an H‐bonding interaction with GLY1185 in the nicotinamide subpocket was lost in case of new compounds ( 12 and 22 ) because of the absence of ‐NH group that is present in known ligands 26 and 27 .…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…between ring keto and SER1221 hydroxyl in the nicotinamide subpocket, amide keto and TYR1213 backbone keto in the adenosine subpocket, while exhibited π‐π stacking/hydrophobic interactions with binding site amino acids, namely TYR1224, HIS1184, PHE1188 and HIS1201. These interactions are reported to be vital for enzyme inhibition based on the X‐ray structures of active compounds . However, as expected, an H‐bonding interaction with GLY1185 in the nicotinamide subpocket was lost in case of new compounds ( 12 and 22 ) because of the absence of ‐NH group that is present in known ligands 26 and 27 .…”
Section: Resultsmentioning
confidence: 55%
“…Recently, tankyrase inhibitors have been identified as useful chemical probes and potential lead compounds . We found that the synthesized compounds possessed similarity with ligands reported as tankyrase‐1 inhibitors binding to both the nicotinamide subpocket and the adenosine subpocket and X‐ray crystal structures (PDB‐ID: 4I9I) are available in the Protein Data Bank (www.rcsb.org). In order to study the putative binding mode of our selected compounds ( 12 and 22 ), we employed flexible docking studies using InducedFit Docking (IFD) modules (Schrödinger suite) into the active site of this enzyme.…”
Section: Resultsmentioning
confidence: 94%
“…Interest in molecules related to the title compound stem from the significant biological activity exhibited by 1,2,4-triazoles [6,7]. This interest prompts investigations into efficient synthesis of these derivatives and in this context, recently two new complementary pathways for the synthesis of N-substituted 3-(5-amino-1H-1,2,4-triazol-3-yl) propanamides based on microwave technology were described [5].…”
Section: Discussionmentioning
confidence: 99%
“…The human tankyrase protein family consists of TNKS-1 and TNKS-2, featuring a catalytic ARTD domain at the C-terminus of 89% of overall sequence identity. The structure has been resolved for the TNKS inhibitor development [38,47,48]. The crystal structures of TNKS-2 in a complex with 3 of 17 XAV939 revealed that the tankyrase inhibitor interacts with the NAD + binding groove of the catalytic domain [49].…”
Section: Preparation For Structure-based Virtual Screeningmentioning
confidence: 99%